A Hyperheuristic Approach for Unsupervised Land-Cover Classification - Papa, Joao Papa [UNESP]; Papa, Luciene Patrici; Pereira, Danillo Roberto [UNESP]; Pisani, Rodrigo Jose (Ieee-inst Electrical Electronics Engineers Inc, 2016)
Unsupervised land-use/cover classification is of great interest, since it becomes even more difficult to obtain high-quality labeled data. Still considered one of the most used clustering techniques, the well-known k-means plays an important role in the pattern recognition community. Its simple formulation and good results in a number of applications have fostered the development of new variants and methodologies to address the problem of minimizing the distance from each dataset sample to its nearest centroid (mean). In this paper, we present a genetic programming-based hyperheuristic approach to combine different metaheuristic techniques used to enhance k-means effectiveness. The proposed approach is evaluated in four satellite and one radar image showing promising results, while outperforming each individual metaheuristic technique.
Keywords: Hyperheuristic; k-means; land-cover classification